1990
DOI: 10.1111/j.1423-0410.1990.tb00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐Cytometric Method for Counting Very Low Numbers of Leukocytes in Platelet Products1

Abstract: We provide a detailed description of a new method for counting very low numbers of leukocytes present in platelet products. The method uses fluorescent staining of leukocyte DNA using propidium iodide and flow cytometry. The assay is accurate over a range of leukocyte concentrations from 0.1 to 10 WBC/microliter. We validated the method using specially designed dilution studies and applied it to the measurement of leukocyte content in leukocyte-depleted platelet products prepared by apheresis or filtration. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 5 publications
3
33
0
Order By: Relevance
“…In addition, 2 min are necessary to input samples/reagent and agitate them, and 5 min for the measurement of each sample. As a result, the measurement of 10 samples takes 105 min [8, 9]. A capillary volumetric cytometry system (IMAGN 2000, Biometric Imaging, Mountain View, Calif., USA) has been developed and widely used in blood centers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 2 min are necessary to input samples/reagent and agitate them, and 5 min for the measurement of each sample. As a result, the measurement of 10 samples takes 105 min [8, 9]. A capillary volumetric cytometry system (IMAGN 2000, Biometric Imaging, Mountain View, Calif., USA) has been developed and widely used in blood centers.…”
Section: Discussionmentioning
confidence: 99%
“…Postfiltration WBCs were measured by flow cytometry using propidium iodide as a DNA marker [23]. This simple method offers lower detection limits, 1 or 2 log below those obtained by the Nageotte chamber.…”
Section: Methodsmentioning
confidence: 99%
“…These two parameters indicated that for Cobe products it was necessary to test every pack prior to release as failures could easily be expected, but for the Haemonetics procedure the parameters indicated that failures were extremely unlikely and that 100% testing was not warranted. White cell counts (WCC) were performed using flow cytometry and propidium staining of DNA as previously described (Dzik et al, 1990).…”
Section: Methodsmentioning
confidence: 99%